รูปแบบเขื่อนป้องกันน้ำท่วมเพื่อวิถีชีวิตชุมชนเมืองริมน้ำ กรณีศึกษา ชุมชนปากคลองมหาสวัสดิ์ กรุงเทพมหานคร - ธฤติ มิระสิงห์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The objective of this research is to study about flood prevention dike patterns on water-based communities, Pakklong Mahasawa community, Bangkok. The researchers wanted to find out the nature of the settlement of the central waterfront community contextual Thailand that it’s characteristic physical and amphibians and a wide range of activities in the areas of the waterfront. How Flood prevention dike is patterns along the line with such a settlement. The hypothesis is flood prevention dike along the diverse forms which have caused (1) physical and social development of the waterfront area will require a different form of flood prevention dike along is different. And (2) the need to interact with different types of events and user groups will need some patterns of flood prevention dike along is different. By survey Questionnaires and in-depth interviews, the accompanying analysis of case studies and guidelines to design a dike on risk areas internationally to establish the sequence and design process. This will contribute to understanding the patterns of vertical dike in the physical and social development of the waterfront area. The study found that the patterns of flood prevention dike along the line with the settlement. Alligator Pattern Thailand should contextual diversity, based on the two; (1) physical and social development of the waterfront area and (2) the need to interact with different types of events and user groups. As can be seen from the defining feature of the landscape and water barrier dike and the physical components to use another format. It’s relative to the level of interaction with water in low level, middle level and high level. It’s different in each community two main types. 1) Urban space and semi- urban agriculture that need protected areas to the water level and require the dam line is designed for use as a public space for the community such waterfront walkway, bike path. Due to the high population density of the area and it’s considered the elements of interconnection transportation by land and sea together. The line feature a water barrier dike found in this area, there’s 2 characteristics; does not allow water to pass through it and allow water to pass through only partially. While 2) the agricultural community, just like adaptive physical elements, especially in the housing for residents with water of genre dike. It should be designed to regard of the physical component housings. The importance is water using for the people such as opening and ladder into the water, mooring dock including connections to route network traffic within the area. Because of low density and demand for water, so feature to stem the tide of discovery along the dike that allows water to pass through only partially that it reduces the severity of the tides both in the community and housing only. The findings led to the recommendation that to design flood protection embankment, it’s consistent with the settlement and reduce the impact on the life of the community at least. In addition, it’s considered of the area to stem the tide with the behavior associated with it and it should still also be designed with an active area of ​​waterfront along the dike as well.